Bond Exchange Offers or Collective Action Clauses? - Ulrich Hege; Pierre Mella-Barral (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
This paper examines two prominent approaches to design efficient mechanisms for debt renegotiation with dispersed bondholders: debt exchange offers that promise enhanced liquidation rights to a restricted number of tendering bondholders (favored under U.S. law), and collective action clauses that allow to alter core bond terms after a majority vote (favored under U.K. law). We use a dynamic contingent claims model with a debt overhang problem, where both hold-out and hold-in problems are present. We show that the former leads to a more efficient mitigation of the debt overhang problem than the latter. Dispersed debt is desirable, as exchange offers also achieve a larger and more efficient debt reduction relative to debt held by a single creditor.
Keywords: 330